Faktor-faktor yang Memengaruhi Pembelian Produk Melalui TV Home Shopping - Maria Tri Rahayu; Budi Suharjo; Lilik Noor Yuliati (School of Business, Bogor Agricultural University (SB-IPB), 2018)
This research aimed to improve better understanding on consumer behavior of TV Home Shopping (THS) by identifying the behavior of consumers watching THS, analyzing the effect of THS on consumer interest in purchasing THS products on consumer groups who have needs and who do not, and giving recommendation on THS program development to increase sales. In this research, the data were taken in the form of surveys through direct interviews using questionnaire as the instrument tool. The research data were processed by PLS smart software. The results showed that the respondents’ profiles as THS product buyers were dominated by women (63%), adults (30-39 years old, 51%), high education background (S1, 50%), full-time workers (56%), and middle to upper class communities (42%). There were three major THS channels chosen by the respondents i.e. OShop (47%), Lejel Home Shopping (37%), and MNC Shop (15%). The results of this research identified the primary reasons of purchasing products in THS i.e. product prices, appealing gifts, unique products, trending products, time saving, high quality products, needs for the products, lower prices, convenience by staying at home, and shopping for pleasure /gifts.Keywords: commercial, TV Home Shopping, AIDAAbstrak: Penelitian ini bertujuan meningkatkan pemahaman yang lebih baik tentang perilaku konsumen TV Home Shopping (THS) dengan mengidentifikasi perilaku masyarakat dalam menonton THS, menganalisis pengaruh THS terhadap minat konsumen dalam membeli produk THS pada kelompok konsumen yang butuh dan belum butuh, dan memberikan rekomendasi pengembangan program THS untuk meningkatkan penjualan. Pada penelitian ini, data diperoleh dengan metode survei melalui wawancara langsung dengan menggunakan bantuan instrumen kuesioner. Data penelitian diolah dengan bantuan software smart PLS. Hasil olah data memperlihatkan profil responden pembeli produk THS dalam penelitian ini sebagian besar adalah wanita (63%) berusia dewasa (30–39 thn, 51%), memiliki pendidikan cukup tinggi (S1, 50%), bekerja full time (56%) dan berkelas menengah atas (42%). Tiga channel THS pilihan utama responden adalah OShop (47%), Lejel Home Shopping (37%), dan MNC Shop (15%). Hasil penelitian tentang prioritas alasan membeli produk berturut-turut adalah harga produk, hadiah yang menarik, produk unik, produk sedang trend, hemat waktu, produk berkualitas, produk dibutuhkan, harga lebih murah, tidak perlu ketoko, beli untuk kesenangan/hadiah.Kata kunci: Iklan, TV Home Shopping, AIDA